El técnico superior en integración social: apuntes sobre su perfil y formación - Pérez Medina, Juan Carlos (Cuadernos de Trabajo Social, 2008)
In this article, the figure of the «Certified Social Integration Technician» is placed in context. This is a certificate which arises from the reform of the educational and vocational training system, contributed by L.O.G.S.E.*, and which, to a great extent, is replacing with specific training and a more formal nature, the «Social Monitors» who worked in different programmes but who, in many instances, did it as volunteer work or without any homogenous training. Going from a general perspective to a more specific one in the training of this technician, the main objective is to place the field of vocational training and its current transformations so as to descend to the Professional Family of Sociocultural and Community Services, to the curriculum and the profile of the aforementioned Social Integration Technician and to the example of the formative development of a module or subject of its training programme, thus showing the suitability of this professional figure in the broad field of Social Services.